Functional outcome of patients with prolonged hypoglycemic encephalopathy - Guillaume Barbara; Bruno Mégarbane; Laurent Argaud; Guillaume Louis; Nicolas Lerolle; Francis Schneider; Stéphane Gaudry; Nicolas Barbarot; Angéline Jamet; Hervé Outin; Sébastien Gibot; Pierre-Edouard Bollaert (Annals of Intensive Care, 2017)
Abstract Background Little is known about the causes, clinical course and long-term outcome of comatose patients with prolonged hypoglycemic encephalopathy. Methods In a multicenter retrospective study conducted in patients hospitalized from July 1, 2004, to July 1, 2014, we investigated functional long-term prognosis and identified prognosis factors of patients admitted in an intensive care unit (ICU) with prolonged neurological manifestations related to hypoglycemia. Eligible patients were adults admitted to the ICU with a Glasgow Coma Score <8 due to hypoglycemia and persistent consciousness disorders after normalizing blood glucose levels. Patients with possible other causes of consciousness disorders, previous cognitive disorders, hypothermia <35 °C or circulatory arrest within 24 h after ICU admission, were excluded. Follow-up phone call was used to determine patients’ functional outcome using modified Rankin Scale (mRS) at a minimum of 1-year follow-up with mRS 0–3 defining good and mRS 4–6 poor outcomes. Results Forty-nine patients were included. Causes of hypoglycemia were various, mainly including insulin or oral antidiabetic drugs abuse (65%) and neuroendocrine carcinoma (16%). Twenty (41%) patients died in the ICU, two (4%) patients further died and nine (18%) patients had a poor outcome at long-term follow-up. Five patients discharged from the ICU with mRS > 3 improved enough to be in the good outcome group 1 year later. Twenty-two (45%) patients underwent therapeutic limitation, mainly related to no expected hope for improvement. On multivariate analysis, only low mRS prior to ICU admission (OR 2.6; 95% CI 1.1–6.3; P = 0.03) and normal brain imaging (OR 7.1; 95% CI 1.1–44; P = 0.03) were significantly predictive of a good outcome. All patients (n = 15) who remained hypoglycemic >480 min had a poor outcome. Conclusion Poor outcome was observed in about 60% of this population of hypoglycemic encephalopathy. However, some patients can recover satisfactorily over time.